When the Spring is not coming: radical Left and social movements in Italy during the austerity era - Castellani, S.; Queirolo-Palmas, L (Challenging austerity radical Left and social movements in the South of Europe, 2017)
At the dawn of the new millennium, Italy experienced a rebirth and re-grouping of leftist movements against neo-liberal globalisation (Global Social Forum, No Tav, No Dal Molin, etc.). The peak of this trend was the collective action and conflict during the G8 summit in Genoa in July 2001. Despite the critical mass, which the movements had in that moment, in less than a decade this political capital was wasted due to internal and external causes. In the middle of the economic crisis, the radical Left did not take to the streets in Italy, whilst in many other countries of Southern Europe affected by crisis and austerity policies imposed by EU institutions, the so-called ‘European Springs’ took place. In turn, a new party, the Five-Star Movement, was born. This chapter analyses the evolution of anti-globalisation movements in Italy and the reasons why these forces did not massively join the anti-austerity protests in the south of Europe, leaving an empty political space to be occupied by other subjects.